Women in the eighteenth century : constructions of femininity - Jones, Vivien, 1952- (World and word series., 1990)
Complementing the current upsurge in feminist writing on the eighteenth century, and giving students the chance to make their own re-readings of texts, this anthology gathers together a range of material from conduct manuals to medical texts.